
2012×20212021−2021×20122012用简便方法?
19个回答
展开全部
解:2012×20212021−2021×20122012
=2012×2021×10001−2021×2012×10001
=0
=2012×2021×10001−2021×2012×10001
=0
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
原式=2012×2021×10001-2021×2012×10001
=10001×(2012×2021-2021×2012)
=10001×0
=0
=10001×(2012×2021-2021×2012)
=10001×0
=0
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
2012×20212021-2021×20122012
=2012×2021×10001-2021×2012×10001
=10001×(2012×2021-2021×2012)
=10001×0
=0
=2012×2021×10001-2021×2012×10001
=10001×(2012×2021-2021×2012)
=10001×0
=0
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
2012×20212021–2021×20122012
=2012×(2021×10001)–2021×(2012×10001)
=2012×2021×10001–2012×2021×10001
=0
=2012×(2021×10001)–2021×(2012×10001)
=2012×2021×10001–2012×2021×10001
=0
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
2012×(20210000+2021)-2021×(20120000+2012)
=2012×2021×1000+2012×2021-2021×2012×1000-2021×2012
=0
=2012×2021×1000+2012×2021-2021×2012×1000-2021×2012
=0
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询